THE QUALITY MANAGEMENT AND THE SAFETY OF PRODUCTS IN CATERING ORGANIZATIONS ON THE BASIS OF THE HACCP PRINCIPLES - Tatiana Victorovna Shchedrina; Timur Shamilyevich Shaltumaev; Natalia Sergeevna Limareva; Valeria Nikolaevna Orobinskaya (Современная наука и инновации, 2022)
The analysis of problems and opportunities of safety and product quality for the population in catering organizations on the basis of modern requirements is carried out in the article.